Genealogy of care in foucault's perspective. - Bertolossi Marta, Cristiano; Rangel Teixeira, Eneas (Revista de Pesquisa: Cuidado é Fundamental)
Objective: identifying the state of the art of care genealogy through publications in national and international journals. Method: this is an integrative review of the process in health care and nursing, preceded between 10th February, 2014 and 20th February, 2014, in the Medline, Lilacs and SciELO of data portals VHL and CAPES. Article 17 was explored and the results were grouped into two categories: the Archeological and Genealogical methods proposed by Michel Foucault and Considerations knowledge and practices of health care and nursing. Results: the care and its relationships have transversality in ways of caring in different forms and spaces. The transversality becomes evident when it comes to body care with direct, indirect and contextual mode, evoking shared knowledge and complex actions. Conclusion: it is necessary to reflect on the production of self-care and implications for health activities, including the philosophy of power involved in this process.